JAEPL, Vol. 14, Winter 2008-2009 - Kristie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
Essays Peter Elbow - The Believing Game or Methodological Believing Nathaniel Teich - The Rhetoric of Empathy: Ethical Foundations of Dialogical Communication Mary Rose O'Reily - Splitting the Cartesian Hair Patricia Bizzell - Faith-Based World Views as a Challenge to the Believing Game Gina Briefs-Elgin - Lessons With the Mystics: Refreshing Our Vision in Mid/Late Career Gesa E. Kirsch - Creating Spaces for Listening, Learning, and Sustaining the Inner Lives of Students Sue Hum - The Persuasiveness of Pleasure: Play, Reciprocity, and Persuasion in Online Discussions Reviews Brad E. Lucas - Teaching Multi writing: Researching and Composing with Multiple Genres, Media, Disciplines, and Cultures Heidi Estrem - CoUege Writing and Beyond: A New Framework for University Writing Instruction Yufeng Zhang - Reading Chinese Fortune Cookie: The Making of Chinese American Rhetoric William FitzGerald - Geographies of Writing: Inhabiting Places and Encountering Difference Connecting - Helen Walker Louise Morgan - Email about the Ego Danielle Sahm - The Poet Rewritten Laurence Musgrove - People Get Ready Rae Ann De Rosse - Authority Issues Joonna Smitherman Trapp - The Importance of Being Ernie Beverly Faxon - Why I Read Them Poetry